The relationship between youtube game content and politeness in children's language - Suroyya, Dewi Asitta; Widayati, Sri; Adhe, Kartika Rinakit; Saroinsong, Wulan Patria; Puspitasari, Tuti (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study is prompted by the politeness of the everyday language used by children who watch YouTube gaming content. The goal of this study is to see if there is a link between YouTube game content and language politeness in children aged 5-6 years. This study employs quantitative correlational research with 52 children aged 5-6 years old from TK Muslimat NU 74 Ketegan and TK Muslimat NU 36 Menyanggong. Product-moment correlation data analysis is used in this study, along with prerequisite tests, normality tests, and linearity testing. The findings of this study reveal that there is a relationship between YouTube game content and language politeness in children aged 5-6 years, with a Pearson correlation r value of 0.763, indicating that the relationship between X and Y variables is high. Another finding is that the two variables have a positive aspect. Children have a larger vocabulary, and they know and understand certain English terms. This is demonstrated by children's increased activity in expressing their feelings and opinions at school.